Online Crossword Puzzle on Young Learners Vocabulary Knowledge - Dahlia, Upi (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2023)
Vocabulary is one of the essential language components in learning the English language. Therefore, the learners must learn vocabulary to be able to master four skills, which are listening, speaking, reading, and writing. Teaching vocabulary to young leaners is considered difficult. As a result, the teacher can use one of the media that can be applied in teaching vocabulary to young learners using an online crossword puzzle game. The aim of this research is to find out the effect whether teaching vocabulary using online crossword puzzle games have a significant effect on vocabulary knowledge for young learners. The research is conducted to the fourth grade students of SDIT-At takwin Sukabumi. Random sampling technique is used to get sample from the population and there are two classes that become the sample in this research. There are 25 students from class IV B and 25 students from class IV C. In conducting the research, quasi-experimental method and one group pre-test and post-test design are used. The data was taken from pre-test and post-test by giving vocabulary test. The data are calculated by using t-test formula. Based on the data calculation, the result of tcalculated is 5.0813 while the level significant of ttable 1.677 and the level significant of 0.05 with the degree of freedom (df) of 48. Therefore, it can be concluded the t-test value is higher that the t-table value (5.0813 1.677). It means that alternative hypothesis (Ha) is accepted, which is the result shows that the students in learning vocabulary with the experimental group has significant effect after giving the treatments using online crossword puzzle game. The students can memorize the word easier because they understand the meaning of the word by engaging in language learning experiences through visual aids.